Gene Editing for Inherited Red Blood Cell Diseases - Quintana-Bustamante, Oscar; Fañanas-Baquero, Sara; Dessy-Rodriguez, Mercedes; Ojeda-Pérez, Isabel; Segovia, Jose-Carlos (Frontiers in Physiology, 2022)
Today gene therapy is a real therapeutic option to address inherited hematological diseases that could be beneficial for thousands of patients worldwide. Currently, gene therapy is used to treat different monogenic hematological pathologies, including several red blood cell diseases such as β-thalassemia, sickle cell disease and pyruvate kinase deficiency. This approach is based on addition gene therapy, which consists of the correction of hematopoietic stem cells (HSCs) using lentiviral vectors, which integrate a corrected version of the altered gene. Lentivirally-corrected HSCs generate healthy cells that compensate for the deficiency caused by genetic mutations. Despite its successful results, this approach lacks both control of the integration of the transgene into the genome and endogenous regulation of the therapeutic gene, both of which are important aspects that might be a cause for concern. To overcome these limitations, gene editing is able to correct the altered gene through more precise and safer approaches. Cheap and easy-to-design gene editing tools, such as the CRISPR/Cas9 system, allow the specific correction of the altered gene without affecting the rest of the genome. Inherited erythroid diseases, such as thalassemia, sickle cell disease and Pyruvate Kinase Deficiency, have been the test bed for these gene editing strategies, and promising results are currently being seen. CRISPR/Cas9 system has been successfully used to manipulate globin regulation to re-activate fetal globin chains in adult red blood cells and to compensate for hemoglobin defects. Knock-in at the mutated locus to express the therapeutic gene under the endogenous gene regulatory region has also been accomplished successfully. Thanks to the lessons learned from previous lentiviral gene therapy research and trials, gene editing for red blood cell diseases is rapidly moving from its proof-of-concept to its first exciting results in the clinic. Indeed, patients suffering from β-thalassemia and sickle cell disease have already been successfully treated with gene editing, which will hopefully inspire the use of gene editing to cure erythroid disorders and many other inherited diseases in the near future.